AWARENESS OF ORAC ASSAY AMONG DENTAL STUDENTS - Masilamani, Nithyanandham; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2019)
The Oxygen Radical Absorption Capacity (ORAC) assay estimates the suppression of peroxyradical mediated oxidation by molecules of concern. This calculates the quality as Trolox equivalent and provides the both repression duration and the degree of oxidation suppression. This same test could be used to calculate the antioxidant capacity of nutrition.The survey was performed for assessing awareness of ORAC assay amongst dental students. This was a questionnaire implemented cross sectional type of survey comprising 100 dental college students in Chennai. A self-designed questionnaire with 10 queries eliciting the knowledge and awareness about applications of ORAC assay techniquewas distributed among dental college students. Questionnaires were circulated through an online website survey planet. The questions explored the awareness on ORAC assay technique, diagnostic indications of ORAC assay technique, limitations of ORAC assay technique and mechanism of ORAC assay technique. After the responses were received from 100 participants, data was collected and analysed. 67% of the respondents were aware about ORAC assay technique .52% were aware of diagnostic indications of ORAC assay technique. 45%% were aware of limitations of ORAC assay technique. 35% were aware of mechanism of ORAC assay technique. The awareness aboutORAC assay technique and its applications were less among dental students. Increased awareness and educational programs should be initiated to spread knowledge about ORAC assay technique among all students and clinicians.